Model for the Development of Science and Humanities Curriculum in Islamic Universities - Alparslan Acikgence (Universitas Darussalam Gontor, 2012)
This paper elaborates the model for the curriculum development of science and humanities for Islamic university. The model is based on the theory of worldview, the process of which begins from learning life structure, world structure and extends to the concept of knowledge, human and value. The last three concepts are sought at university level, yet the curriculum at this level should be directed, at the first place towards scientific mentality. Therefore, students should acquire skills and know-how as well as critical thinking to reach such mentality , rather than to give huge load of courses unnecessarily . With those principles action plan for the curriculum development of our universities should be as follows: Two or three courses at introductory level; Two or three required courses in sub-fields of the students; Two or three elective course in the field of the student; Two courses in Islamic scientific tradition; One or two courses in the methodology and logic of Islamic scientific tradition; Two courses in the philosophy and adab of Islamic scientific tradition; The rest are elective courses such as logic, and introductory courses in philosophy and sociology . To be conversant of Islamic scientific tradition, for example student should be given a good grounding in the history of Islamic scientific tradition. The course to be given for this purpose is not a simple history of science in Islamic civilization; it is rather a course which is designed to teach the historical continuity of Islamic scientific tradition.